Knowledge of God as eternal food for the soul - Vatamanu, Cătălin (Napoca Roots, 2022)
The text discusses the “knowledge of God” concept represented by the Hebrew term daath. The term appears frequently in the sapiential writings of the Old Testament, referring to knowledge gained through various possibilities. It also has a theological character, as God is considered the possessor of knowledge. The expression daath Elohim (“knowledge of God”) holds significant meaning, signifying true faith and obedience to God's teachings. The text emphasizes that true nourishment comes from the Word of God, which is compared to bread, and the revelation of God dwells within individuals. The concept is further developed in the New Testament, with Jesus Christ embodying the Word of God, and believers partake in the Eucharistic meal to experience communion with Christ. The overall message highlights the importance of a deep, inner relationship with God and living by His teachings for spiritual growth and fulfilment.